Dictionary of Pharmaceutical Medicine - Nahler, Gerhard. (Springer Vienna, 2009)
The dictionary contains various terms typically used in pharmaceutical medicine. The 2nd edition reflects the increasing importance of this science and the changing regulatory environment in particular on research and development of new therapies as well as on the conduct of clinical trials, marketing authorisation of new medicinal products and safety aspects including pharmacovigilance. The number of key words has been considerably enlarged and increased to over 1,600 terms; it includes new scientific areas such as gene therapy and proteomics. Furthermore, given the importance of the internet, the new edition contains a list of most important web sites. Similar to the 1st edition, also the book explains about 1,000 abbreviations most commonly used in pharmaceutical medicine. This book will be a valuable tool for professionals in the area of the pharmaceutical industry, medical and pre-clinical research, regulatory affairs, marketing and marketing authorisation of pharmaceuticals.